FISCAL REALITIES UNVEILED: ASSESSING JAMMU AND KASHMIR’S ECONOMY POST-ARTICLE 370 ABROGATION - Sharma, Sachin; Yadav, Sunil; Kumar, Vijay; Jakhar, Babloo (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2025)
Purpose To assess the fiscal transformation of Jammu & Kashmir (J&K) after the abrogation of Article 370 and its reorganization in October 2019, with a focus on changes in resource mobilization and allocation. Design/methodology/approach A comparative analysis of secondary data (2015–16 to 2023–24) examining (a) central transfers as a share of GSDP, (b) own-tax revenue relative to GSDP, and (c) capital expenditure by the former state and through centrally sponsored schemes Findings Post‐2019, central transfers rose from 22% to 28% of GSDP, and own-tax revenue increased from 5% to 9%, indicating better fiscal capacity. Capital spending also rose significantly: state outlays grew from 5% to 11% and CSS spending from 2% to 7% of GSDP. Despite this, under-utilization of grants, particularly in health and education highlights governance and accountability gaps Research limitations/implications The use of secondary data limits understanding of sub-regional disparities and underlying inefficiencies. Future studies could include field surveys and interviews to explore institutional challenges. Originality/value This is one of the first empirical studies on J&K’s fiscal shifts post-reorganization, offering policy-relevant insights for improving transfer mechanisms and institutional capacity to support inclusive development.